Pengaruh kadar ekstrak bawang merah (Allium cepa liliaceae) yang berbeda dengan pengencer Ringer’s dextrose terhadap kualitas semen kambing Peranakan Etawah (PE) - Ongky Dwi Ismianto; Achadiah Rachmawati; Suyadi Suyadi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The purpose of this research was to evaluate the use of onion extract (Allium cepa L) diluted in Ringer’s Dextrose base extender on the semen quality of Peranakan Etawah (PE) buck. Fresh onion was grinded and filtered with filter paper. The filtrate was then inactivated by heating it at 56oC for 10 min to avoid the negative or detrimental effect of its biological activity. The onion filtrate was added to the tube containing Ringer’s–dextrose solution with the concentration of 0%, 1%, 2% and 3% (v/v). Semen was collected with artificial vagina from a healthy selected PE buck reared at the Teaching Farm Laboratory of the Animal Husbandry Faculty Brawijaya University. The semen was diluted with prepared extender to rich the sperm concentration of 75x10 millions/ml. The semen parameters were observed after 1 and 2 hours during storage at room temperature. The results showed that concentration of onion extract (OE) affected the individual sperm motility (P<0.05), sperm viability (P>0.05) and sperm abnormality (P<0.05) during semen evaluation at 1 and 2 hours following the semen dilution time. The highest quality of semen following the dilution was shown by the dilution containing 2% of OE (2 ml/100 ml extender). It was concluded that it was possible to use the OE to improve the semen quality during storage at room temperature. A further study of the use of OE should be conducted to explore more positive effect of OE when it is used in combination with standard semen extender and other technique semen storage such as cold storage or freezing process.   Keywords: semen quality, onion extract, Ringer’s dextrose